Association of Depression, Anxiety, and Stress with Socio-demographic Characteristics among Preoperative Patients at Tertiary Care Hospitals in Karachi - Muhammad Iqbal; Amjad Ali; Tanseer Ahmed; Subia Naz; Abdur Rasheed (Liaquat National Journal of Primary Care, 2024)
Background: The preoperative period is known as one of the disturbing events. It habitually prompts cognitive, physiological, and emotional reactions. Depression, anxiety, and stress are considered emotional states usually found in preoperative surgical patients. Objective: To find out the frequency and association of depression, anxiety, and stress with socio-demographic variables among preoperative patients. Methods: This cross-sectional analytical study of 258 preoperative patients was conducted at Dow University Hospital and Dr. Ruth Pfau Civil Hospital, Karachi from August 01, 2019, to July 31, 2020. Ethical approval was obtained before conducting the study. Depression, Anxiety, and Stress Scale-42 tool was used for the data collection. The data was analyzed by using SPSS version 21. Mean and frequency analyses were performed for demographic characteristics. Moreover, a chi-square test was performed to check the association of socio-demographic characteristics of study participants with depression, anxiety, and stress. Results: The majority of the participants (72.5%) in this study were male and 59.7% were between the ages of 20-35 years. The finding of this study revealed that most of the patients had moderate depression (43.02%), extreme anxiety (54.26%), and moderate stress 36.04%. Significant associations were found for depression with gender and monthly income, with a p-value of 0.035 and 0.003 respectively. Gender (p=0.021) and level of education (p=0.013) were significantly associated with stress levels. Conclusion: This study concluded that patients before surgeries had different levels of depression, anxiety, and stress. Age is the only variable that showed a significant association with stress and depression. Furthermore, anxiety is the only domain that is not significantly associated with any demographic characteristics.